Information protection playbook (Elsevier, 2013)
The primary goal of the Information Protection Playbook is to serve as a comprehensive resource for information protection (IP) professionals who must provide adequate information security at a reasonable cost. It emphasizes a holistic view of IP: one that protects the applications, systems, and networks that deliver business information from failures of confidentiality, integrity, availability, trust and accountability, and privacy. Using the guidelines provided in the Information Protection Playbook, security and information technology (IT) managers will learn how to implement the five functions of an IP framework: governance, program planning, risk management, incident response management, and program administration. These functions are based on a model promoted by the Information Systems Audit and Control Association (ISACA) and validated by thousands of Certified Information Security Managers. The five functions are further broken down into a series of objectives or milestones to be achieved in order to implement an IP framework. The extensive appendices included at the end of the book make for an excellent resource for the security or IT manager building an IP program from the ground up. They include, for example, a board of directors presentation complete with sample slides; an IP policy document checklist; a risk prioritization procedure matrix, which illustrates how to classify a threat based on a scale of high, medium, and low; a facility management self-assessment questionnaire; and a list of representative job descriptions for roles in IP. Emphasizes information protection guidelines that are driven by business objectives, laws, regulations, and industry standardsDraws from successful practices in global organizations, benchmarking, advice from a variety of subject-matter experts, and feedback from the organizations involved with the Security Executive CouncilIncludes 11 appendices full of the sample checklists, matrices, and forms that are discussed in the book.